Porous film, separator for secondary battery, and secondary battery
By adopting a multi-layer film design with a three-layer structure in the secondary battery separation membrane, using a specific proportion of organic resin distribution and specific material combination, the problem of high cost and insufficient performance of the secondary battery separation membrane in the prior art is solved, and a low-cost and high-performance battery separation membrane is realized.
Patent Information
- Application Number
- JP2020198669
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-22
- Filing Date
- 2020-11-30
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-11-30
AI Technical Summary
The prior art is difficult to develop a secondary battery separation membrane with excellent thermal dimensional stability, electrode adhesion and battery performance at low cost.
A multilayer film with a three-layer structure is used, in which the organic resin content of each layer is distributed in a specific proportion, and the organic resin content of the outer layer, the middle layer and the inner layer is between 30% and 60%, 10% and 25% and 30% to 60%, respectively, respectively, and materials such as fluorine-containing (meth)acrylate monomer and hydroxy-containing (meth)acrylate monomer are used in combination.
The secondary battery separation membrane with excellent thermal dimensional stability, electrode adhesion and battery performance is achieved at low cost, ensuring high output and long life of the battery.
Smart Images

Figure 0007647072000001 
Figure 0007647072000002 
Figure 0007647072000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a porous film, a separator for a secondary battery, and a secondary battery. [Background technology]
[0002] 2. Description of the Related Art Secondary batteries such as lithium-ion batteries are widely used in automobile applications such as electric vehicles, hybrid vehicles, and plug-in hybrid vehicles; in portable digital devices such as smartphones, tablets, mobile phones, laptops, digital cameras, digital video cameras, and portable game consoles; power tools, electric motorcycles, and electrically assisted bicycles.
[0003] A lithium-ion battery generally has a configuration in which a positive electrode in which a positive electrode active material is laminated on a positive electrode current collector, a negative electrode in which a negative electrode active material is laminated on a negative electrode current collector, and a secondary battery separator and an electrolyte are interposed between them.
[0004] Polyolefin-based porous substrates are used as separators for secondary batteries. The characteristics required for separators for secondary batteries include a characteristic of containing an electrolyte in the porous structure to enable ion migration, and a shutdown characteristic of stopping discharge by melting the porous structure with heat and stopping ion migration when the lithium-ion battery generates abnormal heat.
[0005] Furthermore, as secondary batteries become higher in capacity and output, high safety is required of separators for secondary batteries, and thermal dimensional stability is required to prevent short circuits caused by contact between the positive and negative electrodes due to thermal shrinkage of the separator at high temperatures.
[0006] Furthermore, in the production process of a secondary battery, in order to maintain the laminate structure when transporting a laminate in which a positive electrode, a separator, and a negative electrode are stacked, or when a wound laminate of a positive electrode, a separator, and a negative electrode is inserted into a cylindrical, square, or other can, the laminate is heat-pressed before being inserted, in order to prevent the shape from being distorted when this is done, or to increase the energy density by putting more of the laminate into the can by heat-pressing, and further, in the case of a laminate type, in order to prevent the shape from being distorted after insertion into an exterior material, adhesion between the separator and the electrodes before being impregnated with the electrolyte is required.
[0007] On the other hand, lithium-ion batteries are also required to have excellent battery characteristics such as high output and long life, and are required to exhibit good battery characteristics that can be sustained without reducing the high output characteristics. Furthermore, there is a demand for providing a secondary battery separator that satisfies the above characteristics at low cost.
[0008] In response to these demands, in Patent Document 1, an adhesive layer formed on a heat-resistant layer is laminated to achieve both adhesion to the electrode and blocking resistance. In Patent Document 2, the particle diameter of the particulate polymer and the particle diameter of the inorganic particles satisfy a specific relationship to enhance adhesion to the electrode. However, the test conditions for the blocking resistance test described in Patent Documents 1 and 2 are insufficient, and under appropriate test conditions, the blocking resistance is insufficient with the technology described in Patent Document 1, and improving the blocking resistance results in insufficient adhesion to the electrode. In addition, the adhesive layer swells by performing heat pressing, filling the voids in the electrode active material and the separator, reducing the porosity, and the ion transport rate is reduced, which also reduces the battery characteristics. Furthermore, since Patent Document 1 is a high-cost secondary battery separator because an adhesive layer is applied on a heat-resistant layer, it is difficult to achieve both thermal dimensional stability, adhesion, and battery characteristics at a low cost with the technology described in Patent Documents 1 and 2. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Patent No. 6191597 [Patent Document 2] International Publication No. 2018 / 034094 Summary of the Invention [Problem to be solved by the invention]
[0010] As mentioned above, the adhesiveness between the electrodes and the separator is required by the hot pressing process in the manufacturing process of the secondary battery.In addition, excellent battery characteristics are also required, and it is necessary to achieve both thermal dimensional stability, adhesiveness, high output characteristics, and long battery life at low cost.
[0011] In view of the above problems, an object of the present invention is to provide a porous film having excellent thermal dimensional stability and adhesion to electrodes, as well as excellent discharge characteristics and cycle characteristics, at low cost. [Means for solving the problem]
[0012] Therefore, the present inventors have conducted extensive research in order to provide a low-cost porous film that has excellent thermal dimensional stability and adhesion to electrodes, and also has excellent battery characteristics. In order to solve the above problems, the porous film of the present invention has the following configuration.
[0013] (1) A porous substrate having a porous layer containing inorganic particles and an organic resin on at least one surface of the porous substrate, the porous layer being divided into three equal parts in the thickness direction, each of which is an inner layer in contact with the porous substrate, an intermediate layer adjacent to the inner layer, and an outer layer adjacent to the intermediate layer, the porous layer satisfying the following (a) to (c): and the organic resin is a mixture containing a polymer containing a fluorine-containing (meth)acrylate monomer, or an organic resin A having a copolymer containing a fluorine-containing (meth)acrylate monomer. , porous film. (a) The content α of the organic resin present in the outer layer is 30% or more and 60% or less of the total organic resin content. (b) the content β of the organic resin present in the intermediate layer is 10% or more and 25% or less of the total organic resin content. (c) the content γ of the organic resin present in the inner layer is 30% or more and 60% or less of the total organic resin content. (2) The porous film according to (1), wherein the organic resin is organic resin particles. ( 3 2.) The organic resin further comprises a binder; (1) or (2) The porous film according to claim 1. ( 4 ) the binder is at least one binder selected from the group consisting of polyamide, polyamideimide, polyimide, polyetherimide, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, polysulfone, polyketone, polyetherketone, polycarbonate, polyacetal, polyvinyl alcohol, polyethylene glycol, cellulose ether, acrylic resin, polyethylene, polypropylene, polystyrene, and urethane; ( 3 ) The porous film described in ( 5 ) the binder is an acrylic resin; ( 3 )or( 4 ) The porous film described in ( 6 ) the organic resin A is a mixture containing a polymer of a fluorine-containing (meth)acrylate monomer and a polymer of a (meth)acrylate monomer having a hydroxyl group, or a copolymer containing a fluorine-containing (meth)acrylate monomer and a (meth)acrylate monomer having a hydroxyl group, and the content of the (meth)acrylate monomer having a hydroxyl group is 1% by mass or more and 30% by mass or less when the total components of the organic resin particles are taken as 100% by mass; ( Any of 1) to (5) The porous film according to claim 1. ( 7 ) the (meth)acrylate monomer having a hydroxyl group has a glass transition temperature of a homopolymer formed from the monomer of -100°C or higher and 0°C or lower; 6 ) The porous film described in ( 8) the organic resin A further contains a monomer having two or more reactive groups per molecule, and the content of the monomer having two or more reactive groups per molecule contained in the organic resin A is 1% by mass or more and 10% by mass or less; ( 6 )or( 7 ) The porous film described in ( 9 ) the monomer having two or more reactive groups per molecule is an alkylene glycol di(meth)acrylate or a urethane di(meth)acrylate; 8 ) The porous film described in ( 10 ) the organic resin contains an organic resin B that does not contain fluorine, (1) to ( 9 ) The porous film according to any one of the above. ( 11 ) the content of inorganic particles contained in the porous layer is 60% by mass or more and 95% by mass or less when the total amount of the components of the porous layer is 100% by mass, (1) to ( 10 ) The porous film according to any one of the above. ( 12 )(1) to ( 11 2. A separator for a secondary battery comprising the porous film according to claim 1. ( 13 )( 12 2. A secondary battery comprising the separator for a secondary battery according to claim 1. Effect of the Invention
[0014] According to the porous film of the present invention, a porous film has a porous substrate and a porous layer containing inorganic particles and an organic resin on at least one side of the porous substrate, and this porous layer is divided into three equal parts in the thickness direction into an inner layer, an intermediate layer, and an outer layer. When this porous layer is divided into three equal parts in the thickness direction into an inner layer, an intermediate layer, and an outer layer, the following is satisfied with respect to the total content of organic resin: (a) the content α of the organic resin present in the outer layer is 30% or more and 60% or less, (b) the content β of the organic resin present in the intermediate layer is 10% or more and 25% or less, and (c) the content γ of the organic resin present in the inner layer is 30% or more and 60% or less. This provides a porous film that has excellent thermal dimensional stability and adhesion to electrodes, and enables the provision of secondary batteries with excellent battery characteristics at low cost. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The porous film of the present invention is a porous film comprising a porous substrate and a porous layer, and a porous layer containing inorganic particles and an organic resin having adhesive properties to electrodes laminated on at least one surface of the porous substrate. The present invention will be described in detail below.
[0016] In this specification, "polymer made of fluorine-containing (meth)acrylate monomer" refers to a homopolymer made of fluorine-containing (meth)acrylate monomer or a copolymer containing fluorine-containing (meth)acrylate monomer. In addition, "organic resin" includes "organic resin A", and "organic resin A" may refer to a homopolymer made of fluorine-containing (meth)acrylate monomer, a homopolymer made of (meth)acrylate monomer having a hydroxyl group, a homopolymer made of monomers constituting a specific monomer group, and a copolymer made of fluorine-containing (meth)acrylate monomer and (meth)acrylate monomer having a hydroxyl group.
[0017] [Porous layer] The porous layer of the present embodiment contains inorganic particles and an organic resin consisting of organic resin A. The organic resin may contain, in addition to organic resin A, a binder and organic resin B as desired.
[0018] The porous layer is divided into three equal parts in the thickness direction, each of which is an inner layer in contact with the porous substrate, an intermediate layer adjacent to the inner layer, and an outer layer adjacent to the intermediate layer. By satisfying the following (a) to (c), the porous film can obtain high adhesion to the electrode, excellent thermal dimensional stability, and excellent battery characteristics. (a) When the content of the organic resin present in the outer layer is α, the value of α is 30% or more and 60% or less, preferably 35% or more and 55% or less, more preferably 40% or more and 50% or less, when the content of all the organic resins constituting the porous layer is 100%. If the value of α is less than 30%, sufficient adhesion to the electrode cannot be obtained. On the other hand, if the value of α is more than 60%, the adhesive strength between the porous layer and the porous substrate decreases, and peeling may occur when the porous layer is attached to the electrode. (b) When the content of the organic resin present in the intermediate layer is β, the value of β is 10% or more and 25% or less, preferably 12% or more and 22% or less, more preferably 15% or more and 20% or less, when the content of all the organic resins constituting the porous layer is 100%. If the value of β is less than 10%, the ion permeability may decrease and the battery characteristics may decrease. On the other hand, if it exceeds 25%, the α value decreases, so sufficient adhesion to the electrode cannot be obtained, and the γ value described later decreases, so that the adhesive strength between the porous layer and the porous substrate decreases, and peeling may occur when the porous layer is adhered to the electrode. (c) When the content of the organic resin present in the inner layer is γ, the value of γ is 30% or more and 60% or less, preferably 35% or more and 55% or less, more preferably 40% or more and 50% or less, when the content of all the organic resins constituting the porous layer is 100%. If the value of γ is less than 30%, the adhesive strength between the porous layer and the porous substrate decreases, and peeling may occur when the porous layer is attached to the electrode. On the other hand, if the value of γ is greater than 60%, the value of α decreases, and sufficient adhesion to the electrode cannot be obtained.
[0019] The porous layer is divided into three equal parts in the thickness direction, that is, an outer layer, an intermediate layer, and an inner layer, the inner layer is a layer including an interface between the porous substrate and the porous layer, the outer layer is the outermost surface of the porous layer and is a layer in contact with the electrode, and the intermediate layer is a layer interposed between the inner layer and the outer layer.
[0020] The organic resin contents α, β and γ in the outer layer, intermediate layer and inner layer can be determined, for example, by observing the cross-section of the porous layer with a field emission scanning electron microscope, a cross-section SEM image and a cross-section SEM-EDX image of carbon elements. Based on the cross-section SEM image, the porous layer is divided into three equal parts in the thickness direction, and each region of the outer layer, intermediate layer and inner layer is determined. The cross-section SEM image and the cross-section SEM-EDX image of carbon elements are superimposed, and the area of the carbon elements due to the organic resin contained in each region of the outer layer, intermediate layer and inner layer is analyzed with image analysis software. The total area of the carbon elements of the obtained outer layer, intermediate layer and inner layer is taken as the total of 100% of the organic resin present in the porous layer, and the area ratio of the carbon elements of the outer layer, intermediate layer and inner layer can be calculated to obtain the organic resin contents α, β and γ.
[0021] (organic resin) (1)Organic resin A In this specification, the porous layer contains an organic resin. The form of the organic resin is not particularly limited, but it is preferable that the organic resin is in the form of organic resin particles. By using the organic resin particles, ion permeability is improved, and battery characteristics are improved.
[0022] The organic resin contains organic resin A. It is preferable that organic resin A has a mixture containing a polymer made of a fluorine-containing (meth)acrylate monomer, or a copolymer containing a fluorine-containing (meth)acrylate monomer. This can reduce the surface free energy of organic resin A, and when a coating liquid containing organic resin A is applied to a porous substrate, organic resin A can be unevenly distributed on the surface side, thereby improving the adhesion of the porous layer to the electrode. In the present invention, "(meth)acrylate" means acrylate and / or methacrylate.
[0023] The polymer made of a fluorine-containing (meth)acrylate monomer contains a repeating unit obtained by polymerizing a fluorine-containing (meth)acrylate. Examples of fluorine-containing (meth)acrylate monomers include 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3,3-pentafluoropropyl (meth)acrylate, 2-(perfluorobutyl)ethyl (meth)acrylate, 3-(perfluorobutyl)-2-hydroxypropyl (meth)acrylate, 2-(perfluorohexyl)ethyl (meth)acrylate, 3-perfluorohexyl-2-hydroxypropyl (meth)acrylate, and 3-(perfluoro-3-methylbutyl)-2-hydroxypropyl (meth)acrylate. acrylate, 1H,1H,3H-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, 1H,1H,7H-dodecafluoroheptyl (meth)acrylate, 1H-1-(trifluoromethyl)trifluoroethyl (meth)acrylate, 1H,1H,3H-hexafluorobutyl (meth)acrylate, 1,2,2,2-tetrafluoro-1-(trifluoromethyl)ethyl (meth)acrylate, 2-(perfluorooctyl)ethyl (meth)acrylate, etc. The fluorine-containing (meth)acrylate monomer may be used alone or in combination of two or more kinds at any ratio.
[0024] The content of the fluorine-containing (meth)acrylate monomer in the organic resin A is preferably more than 20% by mass, more preferably 22% by mass or more, even more preferably 25% by mass or more, and even more preferably 30% by mass or more, when the total components of the organic resin A are taken as 100% by mass. Also, it is preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 60% by mass or less, even more preferably 50% by mass or less, particularly preferably 40% by mass or less, and most preferably 35% by mass or less. By keeping it within the above range, sufficient adhesion to the electrode can be obtained.
[0025] The content of the fluorine-containing (meth)acrylate monomer contained in the organic resin A can be measured using known methods. For example, first, the porous layer is removed from the porous film using an organic solvent such as water and alcohol, and the organic solvent such as water and alcohol is thoroughly dried to obtain the components contained in the porous layer. An organic solvent that dissolves the organic resin components is added to the obtained components to dissolve only the organic resin components. Next, the organic solvent is dried from the solution in which the organic resin components have been dissolved, and only the organic resin components are extracted. The obtained organic resin components are used to measure the amount of the fluorine-containing (meth)acrylate monomer by nuclear magnetic resonance ( 1 H-NMR, 19 F-NMR, 13 It can be calculated from the signal intensity indicating the fluorine-containing (meth)acrylate monomer by C-NMR), infrared absorption spectroscopy (IR), X-ray photoelectron spectroscopy (XPS), X-ray fluorescence spectroscopy (EDX), elemental analysis, pyrolysis gas chromatography mass spectrometer (pyrolysis GC / MS), etc. In particular, after confirming the presence or absence of the fluorine-containing (meth)acrylate monomer by pyrolysis GC / MS, 13 The content of the fluorine-containing (meth)acrylate monomer can be determined by C-NMR (a solid-state NMR sample tube is filled with the organic resin component and an appropriate amount of solvent (deuterated chloroform), and after leaving it overnight, the content is measured by DD / MAS).
[0026] The number of fluorine atoms in the fluorine-containing (meth)acrylate constituting the fluorine-containing (meth)acrylate monomer is preferably 3 or more and 13 or less. More preferably, it is 3 or more and 11 or less, and even more preferably, it is 3 or more and 9 or less. By setting it in the above range, it is possible to achieve both low surface free energy and coatability of the organic resin A. When the number of fluorine atoms is 3 or more, the surface free energy of the organic resin A is sufficiently reduced, and the adhesion to the electrode is sufficient. Furthermore, when the number of fluorine atoms is 13 or less, coatability to a porous substrate is ensured, and productivity is improved.
[0027] The number of fluorine atoms in the fluorine-containing (meth)acrylate can be measured using known methods. For example, first, the porous layer is removed from the porous film using an organic solvent such as water and alcohol, and the organic solvent such as water and alcohol is thoroughly dried to obtain the components contained in the porous layer. An organic solvent that dissolves the organic resin components is added to the obtained components to dissolve only the organic resin components, which are then separated from the inorganic particles. Next, the organic solvent is dried from the solution in which the organic resin components have been dissolved, and only the organic resin components are extracted. The obtained organic resin components are used to perform nuclear magnetic resonance ( 1 H-NMR, 19 F-NMR, 13 It can be calculated from the signal intensity showing the fluorine-containing (meth)acrylate monomer by C-NMR), infrared absorption spectroscopy (IR), X-ray photoelectron spectroscopy (XPS), X-ray fluorescence spectroscopy (EDX), elemental analysis, pyrolysis gas chromatography mass spectrometer (pyrolysis GC / MS), etc. Among these, pyrolysis GC / MS is particularly useful.
[0028] The organic resin A preferably contains a mixture containing a polymer made of a fluorine-containing (meth)acrylate monomer and a polymer made of a (meth)acrylate monomer having a hydroxyl group, or a copolymer containing a fluorine-containing (meth)acrylate monomer and a (meth)acrylate monomer having a hydroxyl group. By containing a mixture containing a polymer made of a (meth)acrylate monomer having a hydroxyl group, or a copolymer containing a fluorine-containing (meth)acrylate monomer and a (meth)acrylate monomer having a hydroxyl group, the glass transition temperature of the organic resin A can be adjusted, and organic resin particles having excellent adhesion to the electrode can be obtained.
[0029] The content of the (meth)acrylate monomer having a hydroxyl group is preferably in the range of 1% by mass or more and 30% by mass or less, when the total components of the organic resin A are taken as 100% by mass. More preferably, it is more than 2% by mass, even more preferably 4% by mass or more, even more preferably 6% by mass or more, particularly preferably 10% by mass or more, particularly preferably more than 10% by mass, and most preferably 12% by mass or more. Also, it is more preferably 25% by mass or less, and even more preferably 20% by mass or less. By making the content of the (meth)acrylate monomer having a hydroxyl group contained in the organic resin A 1% by mass or more, sufficient adhesion with the electrode can be obtained, and the battery characteristics can be improved by improving the affinity with the electrolyte, and the thermal dimensional stability can be improved by improving the adhesion with the porous substrate and inorganic particles. Furthermore, particles having excellent stability after particle formation can be obtained. Furthermore, by making it 30% by mass or less, particles having excellent stability after particle formation can be obtained, and side reactions in the secondary battery can be suppressed, thereby imparting excellent battery characteristics.
[0030] The content of the (meth)acrylate monomer having a hydroxyl group contained in the organic resin A can be measured using a known method. For example, first, the porous layer is removed from the porous film using an organic solvent such as water and alcohol, and the organic solvent such as water and alcohol is thoroughly dried to obtain the components contained in the porous layer. An organic solvent that dissolves the organic resin components is added to the obtained components to dissolve only the organic resin components. Next, the organic solvent is dried from the solution in which the organic resin components have been dissolved, and only the organic resin components are extracted. The obtained organic resin components are used to measure the amount of the organic resin components by nuclear magnetic resonance ( 1 H-NMR, 19 F-NMR, 13 It can be calculated from the signal intensity showing the (meth)acrylate monomer having a hydroxyl group by C-NMR), infrared absorption spectroscopy (IR), X-ray photoelectron spectroscopy (XPS), X-ray fluorescence spectroscopy (EDX), elemental analysis, pyrolysis gas chromatography mass spectrometer (pyrolysis GC / MS), etc. In particular, after confirming the presence or absence of the (meth)acrylate monomer having a hydroxyl group by pyrolysis GC / MS, 13The content of the (meth)acrylate monomer having a hydroxyl group can be determined by C-NMR (a solid-state NMR sample tube is filled with the organic resin component and an appropriate amount of solvent (deuterated chloroform), and after leaving it to stand overnight, measurement is performed by the DD / MAS method).
[0031] Examples of the (meth)acrylate monomer having a hydroxyl group include methacrylic acid esters such as hydroxymethyl methacrylate, 2-hydroxyethyl methacrylate, 3-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 5-hydroxypentyl methacrylate, 6-hydroxyhexyl methacrylate, 7-hydroxyheptysil methacrylate, and 8-hydroxyoctyl methacrylate. The (meth)acrylate monomer having a hydroxyl group may be used alone or in combination of two or more at any ratio. In particular, 2-hydroxyethyl acrylate, 4-hydroxybutyl acrylate, and 2-hydroxypropyl acrylate are preferred.
[0032] The glass transition temperature of the homopolymer made of the (meth)acrylate monomer having a hydroxyl group is preferably -100°C or higher, more preferably -70°C or higher, and even more preferably -50°C or higher. By setting the temperature in the above range, sufficient adhesion to the electrode can be obtained. The glass transition temperature (Tg) of the homopolymer made of the (meth)acrylic acid ester monomer (C) having a hydroxyl group is preferably 0°C or lower, more preferably -10°C or lower, and even more preferably -20°C or lower. Here, the glass transition temperature is the midpoint glass transition temperature measured by differential scanning calorimetry (DSC) according to JIS K7121:2012. The midpoint glass transition temperature is the temperature at the point where a straight line equidistant in the vertical direction from the extended straight line of each baseline intersects with the curve of the stepwise change part of the glass transition.
[0033] It is preferable that the organic resin A further contains a monomer having two or more reactive groups per molecule. It is preferable to contain a polymer made of a monomer having two or more reactive groups per molecule or a copolymer made of a fluorine-containing (meth)acrylate monomer and a monomer having two or more reactive groups per molecule. By containing a polymer made of a monomer having two or more reactive groups per molecule or a copolymer made of a fluorine-containing (meth)acrylate monomer and a monomer having two or more reactive groups per molecule, it is possible to obtain polymer particles having excellent electrolyte resistance with suppressed swelling in the electrolyte and excellent adhesion to the electrode. The term "polymer made of a monomer having two or more reactive groups per molecule" refers to a homopolymer made of a monomer having two or more reactive groups per molecule or a copolymer containing a monomer having two or more reactive groups per molecule.
[0034] The content of the monomer having two or more reactive groups per molecule is preferably 1% by mass or more and 10% by mass or less, when the entire organic resin A is taken as 100% by mass. More preferably, it is 3% by mass or more, even more preferably 5% by mass or more, and particularly preferably 6% by mass or more. Also, it is more preferably 9% by mass or less, and even more preferably 8% by mass or less. By making the content of the monomer having two or more reactive groups per molecule 1% by mass or more, sufficient adhesion to the electrode can be obtained, and by suppressing swelling in an excessive electrolyte, the battery characteristics can be improved. Also, by making it 10% by mass or less, polymer particles with excellent stability can be obtained.
[0035] As the polymer made of a monomer having two or more reactive groups per molecule, a monomer capable of forming a crosslinked structure during polymerization can be used. As the monomer having two or more reactive groups per molecule, it is particularly preferable to use a (meth)acrylate monomer having two or more reactive groups per molecule, and it is more preferable to use alkylene glycol di(meth)acrylate and urethane di(meth)acrylate.
[0036] More specifically, the monomer having two or more reactive groups per molecule includes a monofunctional monomer having a thermal crosslinkable crosslinkable group and one or more olefinic double bonds per molecule, and a polyfunctional monomer having two or more olefinic double bonds per molecule. The number of olefinic double bonds per molecule may be one or more. Examples of the thermal crosslinkable crosslinkable group include an epoxy group, an N-methylolamide group, an oxetanyl group, an oxazoline group, and combinations thereof.
[0037] Examples of the monofunctional monomer having an epoxy group, which is a thermally crosslinkable crosslinkable group, and one or more olefinic double bonds per molecule include unsaturated glycidyl ethers such as vinyl glycidyl ether, allyl glycidyl ether, butenyl glycidyl ether, and o-allylphenyl glycidyl ether; monoepoxides of dienes or polyenes such as butadiene monoepoxide, chloroprene monoepoxide, 4,5-epoxy-2-pentene, 3,4-epoxy-1-vinylcyclohexene, and 1,2-epoxy-5,9-cyclododecadiene; alkenyl epoxides such as 1,4-epoxy-1-butene, 1,2-epoxy-5-hexene, and 1,2-epoxy-9-decene; and glycidyl esters of unsaturated carboxylic acids such as glycidyl acrylate, glycidyl methacrylate, glycidyl crotonate, glycidyl-4-heptenoate, glycidyl sorbate, glycidyl linoleate, glycidyl-4-methyl-3-pentenoate, glycidyl ester of 3-cyclohexenecarboxylic acid, and glycidyl ester of 4-methyl-3-cyclohexenecarboxylic acid.
[0038] Examples of monofunctional monomers having an N-methylol amide group, which is a thermally crosslinkable group, and one or more olefinic double bonds per molecule include (meth)acrylamides having a methylol group, such as N-methylol (meth)acrylamide.
[0039] Examples of the monofunctional monomer having an oxazoline group, which is a thermally crosslinkable crosslinkable group, and one or more olefinic double bonds per molecule include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 2-isopropenyl-5-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline.
[0040] Examples of polyfunctional monomers having two or more olefinic double bonds per molecule include allyl(meth)acrylate, ethylene di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipropylene glycol diallyl ether, polyglycol diallyl ether, triethylene glycol divinyl ether, hydroquinone diallyl ether, tetraallyloxyethane, trimethylolpropane diallyl ether, allyl or vinyl ethers of polyfunctional alcohols other than those mentioned above, triallylamine, methylenebisacrylamide, divinylbenzene, alkylene glycol di(meth)acrylate, and urethane di(meth)acrylate.
[0041] The glass transition temperature of a homopolymer made of a monomer having two or more reactive groups per molecule is preferably -50°C or more and 0°C or less. More preferably, it is -45°C or more and 0°C or less. The glass transition temperature here refers to the midpoint glass transition temperature measured by differential scanning calorimetry (DSC) according to JIS K7121:2012. The midpoint glass transition temperature is the temperature at the point where a straight line equidistant in the vertical direction from the straight line extended from each baseline intersects with the curve of the stepwise change portion of the glass transition.
[0042] In the present invention, the polymer made of a fluorine-containing (meth)acrylate monomer may contain a polymer made of a monomer selected from a specific monomer group. Also, the copolymer containing a fluorine-containing (meth)acrylate monomer may be a copolymer containing a monomer selected from a specific monomer group. By making it into a copolymer containing a monomer selected from a specific monomer group, the surface free energy and glass transition temperature of the organic resin A can be adjusted to predetermined conditions.
[0043] It is also possible to form a core-shell type in which a polymer consisting of a monomer selected from a specific monomer group is used as a core and a copolymer containing a fluorine-containing (meth)acrylate monomer is used as a shell around the core. In this specification, the core-shell type includes not only one in which the core is entirely covered with the shell, but also one in which the core is partially covered and the core and shell coexist.
[0044] Examples of monomers constituting the specific monomer group include unsaturated carboxylic acid monomers, (meth)acrylate monomers, styrene-based monomers, olefin-based monomers, diene-based monomers, and amide-based monomers. Examples of monomers constituting these specific monomer groups include unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid; acrylic acid esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, t-butyl acrylate, pentyl acrylate, neopentyl acrylate, isoamyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, dodecyl acrylate, 2-dimethylaminoethyl acrylate, 2-diethylaminoethyl acrylate, 2-dipropylaminoethyl acrylate, 2-diphenylaminoethyl acrylate, 3-(N,N-dimethylamino)propyl acrylate, n-tetradecyl acrylate, stearyl acrylate, and cyclohexyl acrylate; Methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, isobutyl methacrylate, t-butylcyclohexyl methacrylate, pentyl methacrylate, neopentyl methacrylate, isoamyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, dodecyl methacrylate, 2-dimethylaminoethyl methacrylate, 2-diethylaminoethyl methacrylate, 2-dipropylaminoethyl methacrylate, 2-diphenylaminoethyl methacrylate, 3-(N,N-dimethylamino)propyl methacrylate, n-tetradecyl methacrylate, stearyl methacrylate, and cyclohexyl methacrylate. More preferred are isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, methyl (meth)acrylate, and n-butyl (meth)acrylate.The monomers constituting the specific monomer group may be used alone or in combination of two or more kinds in any ratio.
[0045] The content of the monomer selected from the specific monomer group contained in the organic resin A is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and most preferably 50% by mass or more, when the total components of the organic resin A are taken as 100% by mass. Also, it is preferably 80% by mass or less. More preferably, it is 75% by mass or less, even more preferably 70% by mass or less, and most preferably 65% by mass or less. By making the content of the specific monomer group contained in the organic resin A 20% by mass or more, sufficient adhesion to the electrode can be obtained. Also, by making it 80% by mass or less, swelling in the electrolyte can be suppressed, and excellent battery characteristics can be obtained.
[0046] Among the specific monomer groups, it is preferred that at least one of the (meth)acrylate monomers is a (meth)acrylate monomer having a monocyclic cyclic hydrocarbon group or a (meth)acrylate monomer unit substituted with one or more alkyl groups, for the purpose of reducing particle fusion during the preparation of the organic resin A. In the case of a (meth)acrylate monomer having a monocyclic cyclic hydrocarbon group, the reduction in particle fusion is significant, and therefore it is more preferred.
[0047] The content of the acrylate monomer having a monocyclic cyclic hydrocarbon group and the methacrylate monomer having a monocyclic cyclic hydrocarbon group contained in the organic resin A is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and most preferably 50% by mass or more, when the total components of the organic resin A are taken as 100% by mass. Also, it is preferably 80% by mass or less, more preferably 75% by mass or less, even more preferably 70% by mass or less, and most preferably 65% by mass or less. By making the content of the (meth)acrylate monomer having a monocyclic cyclic hydrocarbon group contained in the organic resin A 20% by mass or more, sufficient adhesion to the electrode can be obtained. Also, by making it 80% by mass or less, swelling in the electrolyte can be suppressed, and excellent battery characteristics can be obtained.
[0048] Furthermore, for the purpose of adjusting the glass transition temperature to a predetermined temperature or for the purpose of increasing chemical resistance to the chain carbonate constituting the nonaqueous electrolyte of the secondary battery, the organic resin A may contain monomers such as styrene-based monomers such as styrene, α-methylstyrene, paramethylstyrene, t-butylstyrene, chlorostyrene, chloromethylstyrene, and hydroxymethylstyrene, olefin-based monomers such as ethylene and propylene, diene-based monomers such as butadiene and isoprene, and amide-based monomers such as acrylamide. Of these, one type may be used alone, or two or more types may be used in combination at any ratio.
[0049] The polymerization method of the homopolymer made of a fluorine-containing (meth)acrylate monomer and the copolymer containing a fluorine-containing (meth)acrylate monomer, which forms the organic resin A, is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. may be used. As the polymerization method, any method such as ionic polymerization, radical polymerization, living radical polymerization, etc. may be used. An aqueous solution in which the organic resin A is dispersed in an aqueous solvent is obtained by polymerization. The aqueous solution thus obtained may be used as it is, or the organic resin A may be extracted from the aqueous solution and used. The organic resin preferably contains a monomer that arbitrarily constitutes a specific monomer group, and by forming a copolymer, it is possible to suppress swelling in an electrolytic solution and improve adhesive strength.
[0050] In the polymerization, examples of the emulsifier include cationic surfactants, anionic surfactants, nonionic surfactants, amphoteric surfactants, etc. Among these, one type may be used alone, or two or more types may be used in combination.
[0051] Examples of the cationic surfactant include alkylpyridinium chloride, alkyltrimethylammonium chloride, dialkyldimethylammonium chloride, and alkyldimethylbenzylammonium chloride.
[0052] Examples of the anionic surfactant include sodium alkyl sulfate, sodium alkylbenzene sulfonate, sodium succinate dialkyl ester sulfonate, sodium alkyl diphenyl ether disulfonate, sodium polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene alkyl phenyl ether sulfate, etc. Among these, sodium lauryl sulfate, sodium dodecylbenzene sulfonate, sodium polyoxyethylene alkyl ether sulfate, sodium lauryl sulfate, etc. are preferred.
[0053] Examples of nonionic surfactants include polyoxyethylene alkyl ethers, polyoxyethylene alkylaryl ethers, polyoxyethylene fatty acid esters, polyoxyethylene sorbitan fatty acid esters, etc. In general, polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, etc. are used.
[0054] Examples of amphoteric surfactants include lauryl betaine, sodium hydroxyethyl imidazoline sulfate, and sodium imidazoline sulfonate.
[0055] In addition, as the emulsifier, fluorine-based surfactants such as perfluoroalkyl carboxylates, perfluoroalkyl sulfonates, perfluoroalkyl phosphates, perfluoroalkyl polyoxyethylenes, perfluoroalkyl betaines, and perfluoroalkoxy fluoroammonium carboxylates can also be used.
[0056] Furthermore, so-called reactive emulsifiers copolymerizable with fluorine-containing (meth)acrylate monomers, such as sodium styrenesulfonate, sodium allylalkylsulfonate, polyoxyethylene alkylallyl phenyl ether ammonium sulfate, polyoxyethylene alkylallyl phenyl ether, etc., can be used, and in particular, a combination of 2-(1-allyl)-4-nonylphenoxy polyethylene glycol sulfate ammonium salt and 2-(1-allyl)-4-nonylphenoxy polyethylene glycol is preferred.
[0057] The amount of the emulsifier used is preferably 0.05 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the total amount of the monomers contained in the organic resin A.
[0058] As the polymerization initiator, water-soluble polymerization initiators such as sodium persulfate, potassium persulfate, ammonium persulfate, and hydrogen peroxide, or redox-based polymerization initiators in which these water-soluble polymerization initiators are combined with a reducing agent, can be used. Among these, potassium persulfate and ammonium persulfate are preferred. Examples of reducing agents include sodium pyrobisulfite, sodium hydrogensulfite, sodium sulfite, sodium thiosulfate, L-ascorbic acid or a salt thereof, sodium formaldehyde sulfoxylate, ferrous sulfate, and glucose. Among these, L-ascorbic acid or a salt thereof is preferred.
[0059] The amount of the polymerization initiator used is preferably 0.1 parts by mass or more and 3 parts by mass or less per 100 parts by mass of the total amount of the monomers contained in the organic resin A.
[0060] In this specification, the organic resin A is preferably in a particulate form, and may be referred to as organic resin particles A. In addition to those having a particulate form, the organic resin particles A also include those that are partially filmed and fused with surrounding particles and binders. The shape is not particularly limited, and may be any of spherical, polygonal, flat, fibrous, etc.
[0061] The average particle size of the organic resin particles A is preferably 0.01 μm or more. More preferably, it is 0.082 μm or more, even more preferably, it is 0.10 μm or more, and most preferably, it is 0.12 μm or more. In addition, it is preferably 5 μm or less, more preferably, it is 1 μm or less, even more preferably, it is 0.5 μm or less, and most preferably, it is 0.3 μm or less. By making the average particle size 0.01 μm or more, a porous structure is formed, and the battery characteristics are improved. In addition, by making it 5 μm or less, the film thickness of the porous layer becomes appropriate, and the deterioration of the battery characteristics can be suppressed.
[0062] The average particle size of the organic resin particles A can be measured using the following method. Using a field emission scanning electron microscope (S-3400N manufactured by Hitachi, Ltd.), an image of the surface of the porous layer at a magnification of 30,000 times and an EDX image of elements contained only in the inorganic particles placed on the porous layer consisting of inorganic particles and organic resin particles are obtained. The image size is 4.0 μm × 3.0 μm, the number of pixels is 1,280 pixels × 1,024 pixels, and the size of one pixel is 3.1 nm × 2.9 nm. Particles other than inorganic particles in the obtained EDX image are considered to be the organic resin particles A of the present invention. When they cannot be distinguished by visual observation, those that contain fluorine element by elemental analysis are considered to be organic resin particles A. A square or rectangle with the smallest area that completely surrounds one particle is drawn on the image, that is, a square or rectangle with the ends of the particle touching the four sides of the square or rectangle is drawn, and the length of one side in the case of a square, and the length of the long side in the case of a rectangle (major axis diameter) are taken as the particle size, and the particle size of each of the organic resin particles A on the image is measured, and the arithmetic average value is taken as the average particle size. If 50 organic resin particles A were not observed in the captured image, multiple images were taken and the organic resin particles A were measured so that the total number of organic resin particles A contained in the multiple images was 50 or more, and the arithmetic average value was used as the average particle size.
[0063] From the viewpoint of adhesion to the electrode, the organic resin A is preferably an organic resin that does not contain an inorganic component. By forming the organic resin A in the form of organic resin particles, it may be possible to impart stronger adhesion to the electrode.
[0064] The glass transition temperature of the organic resin A is preferably 20°C or higher. More preferably, it is 25°C or higher, even more preferably, it is 30°C or higher, and most preferably, it is 35°C or higher. Also, it is preferably 60°C or lower, more preferably, it is 55°C or lower, even more preferably, it is 50°C or lower, and most preferably, it is 45°C or lower. By setting the glass transition temperature to 20°C or higher, swelling in the electrolyte is suppressed, and the battery characteristics become good. Also, by setting it to 60°C or lower, the adhesion to the electrode becomes good. In order to set the glass transition temperature in an appropriate range, it can be appropriately selected from a specific monomer group.
[0065] (2) Binder In order to adhere the organic resins to each other or to the inorganic particles, and to adhere the organic resin to the porous substrate, the organic resin may contain a binder in addition to the organic resin A. The binder is preferably a resin that is electrochemically stable within the range of use of the battery. Examples of the binder include binders that are soluble in organic solvents, water-soluble binders, and emulsion binders, and may be used alone or in combination.
[0066] When using a binder soluble in an organic solvent or a water-soluble binder, the preferred viscosity of the binder itself is 10,000 mPa·s or less when the concentration is 15% by mass. More preferably, it is 8,000 mPa·s or less, and even more preferably, it is 5,000 mPa·s or less. By making the viscosity 10,000 mPa·s or less when the concentration is 15% by mass, it is possible to suppress an increase in the viscosity of the coating material, and the organic resin A is unevenly distributed on the surface, thereby improving adhesion to the electrode.
[0067] In addition, when an emulsion binder is used, the dispersant may be water or an organic solvent, such as an alcohol solvent such as ethanol, or a ketone solvent such as acetone, but a water dispersion is preferred in terms of ease of handling and mixability with other components. The particle size of the emulsion binder is 30 to 1000 nm, preferably 50 to 500 nm, more preferably 70 to 400 nm, and even more preferably 80 to 300 nm. By setting the particle size of the emulsion binder to 30 nm or more, the increase in air permeability can be suppressed, and the battery characteristics become good. Furthermore, by setting the particle size to 1000 nm or less, sufficient adhesion between the porous layer and the porous substrate can be obtained.
[0068] Examples of resins used in the binder include polyamide, polyamideimide, polyimide, polyetherimide, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, polysulfone, polyketone, polyetherketone, polycarbonate, polyacetal, polyvinyl alcohol, polyethylene glycol, cellulose ether, acrylic resin, polyethylene, polypropylene, polystyrene, and urethane. From the viewpoint of compatibility with organic resins and electrical stability, it is preferable to use acrylic resin. These resins may be used alone or in a mixture of two or more types as necessary.
[0069] When a water-soluble binder is used, the amount added is preferably 0.5% by mass or more relative to the total amount of the organic resin A and the inorganic particles. More preferably, it is 1% by mass or more, and even more preferably, it is 1.5% by mass or more. Also, it is preferably 10% by mass or less. More preferably, it is 8% by mass or less, and even more preferably, it is 6% by mass or less. By setting the amount of the water-soluble binder to 0.5% by mass or more, sufficient adhesion between the porous layer and the porous substrate can be obtained. Also, by setting it to 10% by mass or less, it is possible to suppress an increase in air permeability, and the battery characteristics become good.
[0070] When an emulsion binder is used, the amount of the emulsion binder added is preferably 1% by mass or more relative to the total amount of the organic resin A and the inorganic particles. More preferably, it is 5% by mass or more, and even more preferably, it is 7.5% by mass or more. Also, it is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less. By setting the amount of the emulsion binder added to 1% by mass or more, sufficient adhesion between the porous layer and the porous substrate can be obtained. Also, by setting it to 30% by mass or less, it is possible to suppress an increase in air permeability, and the battery characteristics become good. In particular, by setting it to 7.5% by mass or more and 20% by mass or less, not only is adhesion between the organic resin A and the inorganic particles and the adhesion of these particles to the substrate promoted, but also an interaction with the organic resin A is exhibited, and the adhesion to the electrode is improved.
[0071] By containing the organic resin and the binder in the above-mentioned amount, the surface free energy of the organic resin can be adjusted, and when a coating liquid containing the organic resin is applied to a porous substrate, the organic resin is promoted to be unevenly distributed not only in the outer layer but also in the inner layer.
[0072] (3)Organic resin B As the electrode adhesion assistant and the substrate adhesion assistant, the organic resin may contain, in addition to the organic resin A and the binder, an organic resin B that does not contain fluorine. When the organic resin B is contained, it interacts with the organic resin A, and a part of it is unevenly distributed on the surface, which may improve the adhesion between the porous layer and the electrode. In addition, it may be present at the interface between the porous layer and the porous substrate, which may improve the substrate adhesion. The resin used for the organic resin B is a resin that does not contain fluorine, such as acrylic resin, polyethylene, polypropylene, polystyrene, and urethane. In terms of adhesion to the electrode and adhesion to the porous substrate, it is preferable to use acrylic resin, polyethylene, and polypropylene. In addition, the glass transition temperature of the organic resin B is preferably 10°C or higher. More preferably, it is 20°C or higher, more preferably 30°C or higher, and most preferably 40°C or higher. In addition, it is preferably 100°C or lower. More preferably, it is 90°C or lower, more preferably 80°C or lower, and most preferably 70°C or lower. By setting the glass transition temperature to 10°C or higher, swelling in the electrolyte can be suppressed, and the battery characteristics are improved. Furthermore, by setting the temperature at 100° C. or less, sufficient adhesion to the electrode and adhesion to the porous substrate can be obtained.
[0073] The amount of organic resin B added is preferably 0.1% by mass or more based on the total amount of organic resin A and inorganic particles. More preferably, it is 0.3% by mass or more, even more preferably, it is 0.5% by mass or more, and most preferably, it is 1.0% by mass or more. Also, it is preferably 30% by mass or less, more preferably, it is 25% by mass or less, even more preferably, it is 20% by mass or less, even more preferably, it is 10% by mass or less, particularly preferably, it is 5% by mass or less, and most preferably, it is 3% by mass or less. By making the amount of organic resin B added 0.1% by mass or more, sufficient adhesion with the electrode can be obtained, and sufficient adhesion between the porous layer and the porous substrate can be obtained. Also, by making it 30% by mass or less, it is possible to suppress an increase in air permeability, and the battery characteristics become good.
[0074] The organic resin B is preferably in the form of particles, and is preferably organic resin particles B. The particle size is preferably 10 nm or more. More preferably, it is 30 nm or more, even more preferably 50 nm or more, even more preferably 80 nm or more, and most preferably 100 nm or more. Also, it is preferably 500 nm or less, more preferably 400 nm or less, even more preferably 300 nm or less, even more preferably 250 nm or less, particularly preferably 200 nm or less, and most preferably 150 nm or less. By making the particle size of the organic resin particles B 10 nm or more, it is possible to suppress an increase in air permeability, and the battery characteristics are improved. Also, by making it 500 nm or less, it is unevenly distributed on the surface, and sufficient adhesion is obtained.
[0075] (Inorganic particles) In the present invention, the porous layer preferably contains inorganic particles, which can provide thermal dimensional stability and suppress short circuits caused by foreign matter.
[0076] Specific examples of inorganic particles include inorganic oxide particles such as aluminum oxide, boehmite, silica, titanium oxide, zirconium oxide, iron oxide, and magnesium oxide, inorganic nitride particles such as aluminum nitride and silicon nitride, and sparingly soluble ion crystal particles such as calcium fluoride, barium fluoride, and barium sulfate. Among inorganic particles, aluminum oxide, which is effective in increasing strength, and boehmite and barium sulfate, which are effective in reducing wear of parts during the dispersion process of the organic resin particles A and the inorganic particles, are particularly preferred. Furthermore, these inorganic particles may be used alone or in combination of two or more types.
[0077] The average particle diameter of the inorganic particles used is preferably 0.05 μm or more. More preferably, it is 0.10 μm or more, and even more preferably, it is 0.20 μm or more. Also, it is preferably 5.0 μm or less. More preferably, it is 3.0 μm or less, even more preferably, it is 1.0 μm or less, and particularly preferably, it is 0.6 μm or less. By making it 0.05 μm or more, the increase in air permeability can be suppressed, and the battery characteristics are improved. In addition, since the pore diameter becomes small, the impregnation of the electrolyte solution may decrease, which may affect productivity. By making it 5.0 μm or less, not only is sufficient thermal dimensional stability obtained, but the film thickness of the porous layer becomes appropriate, and the deterioration of the battery characteristics can be suppressed.
[0078] The average particle size of the inorganic particles was measured and obtained using the following method. Using a field emission scanning electron microscope (S-3400N manufactured by Hitachi, Ltd.), an image of the surface of the porous layer at a magnification of 30,000 times and an EDX image of elements contained only in the inorganic particles placed in the porous layer consisting of inorganic particles and organic resin particles were obtained. The image size was 4.0 μm × 3.0 μm. The number of pixels was 1,280 pixels × 1,024 pixels, and the size of one pixel was 3.1 nm × 2.9 nm. Next, a square or rectangle with the smallest area that completely surrounds one of the inorganic particles identified from the obtained EDX image was drawn, that is, a square or rectangle with the ends of the particle touching the four sides of the square or rectangle was drawn, and the particle size of each of the inorganic particles on the image was measured using the length of one side in the case of a square and the length of the long side (major axis diameter) in the case of a rectangle, and the arithmetic average value was taken as the average particle size. In addition, if 50 particles were not observed in the captured image, multiple images were taken and the inorganic particles were measured so that the total number of inorganic particles contained in the multiple images was 50 or more, and the arithmetic average value was used as the average particle size.
[0079] The shape of the inorganic particles used may be any shape, including spherical, plate-like, needle-like, rod-like, elliptical, etc. Among these, spherical shapes are preferred from the viewpoints of surface modification, dispersibility, and coatability.
[0080] (Formation of porous layer) The porous film of the present invention has a porous substrate and a porous layer containing inorganic particles and an organic resin on at least one side of the porous substrate, and when this porous layer is divided into three equal parts in the thickness direction, designated as an inner layer, an intermediate layer, and an outer layer, the content of all organic resins satisfies: (a) the content α of the organic resin present in the outer layer is 30% or more and 60% or less, (b) the content β of the organic resin present in the intermediate layer is 10% or more and 25% or less, and (c) the content γ of the organic resin present in the inner layer is 30% or more and 60% or less.
[0081] By forming such a porous film, a low-cost porous film having excellent thermal dimensional stability and adhesion to electrodes, as well as excellent battery characteristics, can be obtained. A method for forming the porous layer is described below.
[0082] The porous layer contains an organic resin and inorganic particles. The organic resin is made of organic resin A and may optionally contain a binder and organic resin B. When the total components of the porous layer are taken as 100% by mass, the porous layer preferably contains 2% by mass or more of organic resin A. Also, the organic resin preferably contains 30% by mass or less. The organic resin A is more preferably 4% by mass or more. Also, the organic resin A is more preferably 20% by mass or less, and further preferably 15% by mass or less. By making the content of organic resin A in the porous layer 2% by mass or more, sufficient adhesion to the electrode can be obtained. Also, by making the content of organic resin A in the porous layer 30% by mass or less, sufficient thermal dimensional stability can be obtained. The content of organic resin A in the porous layer can be measured by a known method. For example, first, the porous layer is detached from the porous film using an organic solvent such as water and alcohol, and the organic solvent such as water and alcohol is thoroughly dried to obtain the components contained in the porous layer. After measuring the mass of the total amount of the obtained components, an organic solvent that dissolves the organic resin components is added to the obtained components to dissolve only the organic resin components. Next, the organic solvent is dried from the solution in which the organic resin component is dissolved, and only the organic resin component is extracted. The obtained organic resin component is used for nuclear magnetic resonance ( 1 H-NMR, 19The mass of only particle A is measured by F-NMR), infrared absorption spectroscopy (IR), X-ray photoelectron spectroscopy (XPS), X-ray fluorescence spectroscopy (EDX), gas chromatography mass spectrometry, matrix-assisted laser desorption / ionization time-of-flight mass spectrometry (MALDI-TOF-MS), elemental analysis, etc. The content of organic resin A in the porous layer can be calculated using the formula (mass of organic resin A / mass of all components) x 100.
[0083] The content of inorganic particles in the porous layer is preferably 60% by mass or more, more preferably 65% by mass or more, even more preferably 70% by mass or more, and most preferably 75% by mass or more, when the total components of the porous layer are 100% by mass. Also, it is preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less. By making the content of inorganic particles in the porous layer 60% by mass or more, sufficient thermal dimensional stability is obtained. Also, by making the content of particles B in the porous layer 95% by mass or less, the content of organic resin becomes sufficient, and adhesion to the electrode is obtained.
[0084] The organic resin constituting the porous layer is dispersed to a predetermined concentration to prepare an aqueous dispersion coating liquid. The aqueous dispersion coating liquid is prepared by dispersing, suspending, or emulsifying the organic resin in a solvent. At least water is used as the solvent for the aqueous dispersion coating liquid, and a solvent other than water may be added. The solvent other than water is not particularly limited as long as it does not dissolve the organic resin and can disperse, suspend, or emulsify it in a solid state. For example, organic solvents such as methanol, ethanol, 2-propanol, acetone, tetrahydrofuran, methyl ethyl ketone, ethyl acetate, N-methylpyrrolidone, dimethylacetamide, dimethylformamide, and dimethylformamide can be mentioned. From the viewpoints of low environmental load, safety, and economics, an aqueous emulsion in which an organic resin is emulsified in water or a mixture of water and alcohol is preferable. By appropriately adjusting the concentration of the aqueous dispersion coating liquid, the organic resin A can be adjusted to be unevenly distributed in the outer layer.
[0085] If necessary, a film-forming assistant, a dispersant, a thickener, a stabilizer, an antifoaming agent, a leveling agent, etc. may be added to the coating liquid.
[0086] Examples of the method for dispersing the coating liquid include a ball mill, a bead mill, a sand mill, a roll mill, a homogenizer, an ultrasonic homogenizer, a high-pressure homogenizer, an ultrasonic device, a paint shaker, etc. A plurality of these mixers and dispersers may be combined to perform dispersion in stages.
[0087] Next, the obtained coating liquid is applied onto a porous substrate, dried, and a porous layer is laminated. Coating methods include, for example, dip coating, gravure coating, slit die coating, knife coating, comma coating, kiss coating, roll coating, bar coating, spray coating, immersion coating, spin coating, screen printing, inkjet printing, pad printing, and other types of printing. The coating method is not limited to these, and may be selected according to the preferred conditions of the organic resin, binder, dispersant, leveling agent, solvent, substrate, etc. used. In addition, in order to improve the coatability, the porous substrate may be subjected to surface treatment of the coating surface, such as corona treatment and plasma treatment.
[0088] The thickness of the porous layer is preferably 1.0 μm or more. More preferably, it is greater than 1.0 μm, even more preferably 2.0 μm or more, even more preferably 2.5 μm or more, and most preferably 4.0 μm or more. Also, it is preferably 10.0 μm or less. More preferably, it is 8.0 μm or less, even more preferably 7.0 μm or less, even more preferably 6.0 μm or less, and particularly preferably 5.0 μm or less. The thickness of the porous layer here refers to the thickness of the porous layer in the case of a porous film having a porous layer on one side of a porous substrate, and refers to the sum of the thicknesses of both porous layers in the case of a porous film having a porous layer on both sides of a porous substrate. By making the thickness of the porous layer 1.0 μm or more, sufficient thermal dimensional stability and adhesion to the electrode can be obtained. Also, by making it 10.0 μm or less, a porous structure is formed and the battery characteristics are good. It is also advantageous in terms of cost.
[0089] [Porous base material] In this embodiment, the porous substrate is a substrate having pores therein. In addition, in this embodiment, examples of the porous substrate include a porous membrane having pores therein, a nonwoven fabric, or a porous membrane sheet made of a fibrous material. The material constituting the porous substrate is preferably made of a resin that is electrically insulating, electrically stable, and stable in an electrolyte. In addition, from the viewpoint of imparting a shutdown function, the resin used is preferably a thermoplastic resin having a melting point of 200° C. or less. The shutdown function here refers to a function that, when a lithium ion battery generates abnormal heat, closes the porous structure by melting with heat, stops ion migration, and stops power generation.
[0090] The thermoplastic resin may be, for example, a polyolefin-based resin, and the porous substrate is preferably a polyolefin-based porous substrate.Moreover, the polyolefin-based porous substrate is more preferably a polyolefin-based porous substrate with a melting point of 200°C or less.Specific examples of the polyolefin-based resin include polyethylene, polypropylene, ethylene-propylene copolymer, and mixtures of these.For example, a single-layer porous substrate containing 90% by mass or more of polyethylene, and a multi-layer porous substrate made of polyethylene and polypropylene may be mentioned.
[0091] Methods for producing a porous substrate include a method in which a polyolefin resin is formed into a sheet and then stretched to make it porous, and a method in which a polyolefin resin is dissolved in a solvent such as liquid paraffin, formed into a sheet, and then the solvent is extracted to make it porous.
[0092] The thickness of the porous substrate is preferably 3 μm or more and 50 μm or less, more preferably 5 μm or more and 30 μm or less. By making the thickness of the porous substrate 50 μm or less, an increase in the internal resistance of the porous substrate can be suppressed. In addition, by making the thickness of the porous substrate 3 μm or more, it becomes possible to manufacture the porous substrate, and sufficient mechanical properties can be obtained.
[0093] The thickness of the porous substrate can be measured by observing the cross section with a microscope. When a porous layer is laminated, the vertical distance between the interface between the porous substrate and the porous layer is measured as the thickness of the porous substrate. Five pieces of 100 mm x 100 mm in size are cut out, and the central part of each of the five samples is observed and measured, and the average value is taken as the thickness of the porous substrate.
[0094] The air permeability of the porous substrate is preferably 50 sec / 100cc or more and 1,000 sec / 100cc or less. More preferably, it is 50 sec / 100cc or more and 500 sec / 100cc or less. When the air permeability is 1,000 sec / 100cc or less, sufficient ion mobility can be obtained, and the battery characteristics can be improved. When the air permeability is 50 sec / 100cc or more, sufficient mechanical characteristics can be obtained.
[0095] [Porous film] The porous film of this embodiment is a porous film having the above-mentioned porous layer on at least one side of the porous substrate. The porous layer is preferably sufficiently porous to have ion permeability, and the air permeability of the porous film is preferably 50 sec / 100cc or more and 1,000 sec / 100cc or less. More preferably, it is 50 sec / 100cc or more and 500 sec / 100cc or less. Even more preferably, it is 50 sec / 100cc or more and 300 sec / 100cc or less. When the air permeability is 1,000 sec / 100cc or less, sufficient ion mobility can be obtained, and the battery characteristics can be improved. When it is 50 sec / 100cc or more, sufficient mechanical properties can be obtained.
[0096] [Secondary battery] The porous film of the present embodiment can be suitably used as a separator for secondary batteries such as lithium ion batteries. A lithium ion battery has a configuration in which a secondary battery separator and an electrolyte are interposed between a positive electrode in which a positive electrode active material is laminated on a positive electrode current collector and a negative electrode in which a negative electrode active material is laminated on a negative electrode current collector.
[0097] The positive electrode is a positive electrode material consisting of an active material, a binder resin, and a conductive assistant layered on a current collector. Examples of the active material include layered lithium-containing transition metal oxides such as LiCoO2, LiNiO2, and Li(NiCoMn)O2, spinel-type manganese oxides such as LiMn2O4, and iron-based compounds such as LiFePO4. As the binder resin, a resin with high oxidation resistance may be used. Specific examples include fluororesin, acrylic resin, and styrene-butadiene resin. Carbon materials such as carbon black and graphite are used as the conductive assistant. Metal foil is suitable as the current collector, and aluminum foil is often used in particular.
[0098] The negative electrode is a current collector on which negative electrode materials consisting of active materials and binder resins are laminated. The active materials include carbon materials such as artificial graphite, natural graphite, hard carbon, and soft carbon, lithium alloy materials such as tin and silicon, metal materials such as Li, and lithium titanate (Li4Ti5O 12 ) and the like. As the binder resin, fluororesin, acrylic resin, styrene-butadiene resin, and the like are used. As the current collector, a metal foil is suitable, and in particular, copper foil is often used.
[0099] The electrolyte is a place where ions move between the positive and negative electrodes in the secondary battery, and is composed of an electrolyte dissolved in an organic solvent. Examples of the electrolyte include LiPF6, LiBF4, and LiClO4, and LiPF6 is preferably used from the viewpoint of solubility in organic solvents and ionic conductivity. Examples of the organic solvent include ethylene carbonate, propylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, and two or more of these organic solvents may be mixed and used.
[0100] In the method of producing a secondary battery, first, an active material and a conductive assistant are dispersed in a binder resin solution to prepare an electrode coating solution, and the coating solution is applied onto a current collector, and the solvent is dried to obtain a positive electrode and a negative electrode. The thickness of the coating film after drying is preferably 50 μm to 500 μm. A separator for a secondary battery is placed between the obtained positive electrode and negative electrode so as to contact the active material layer of each electrode, and the separator is enclosed in an exterior material such as an aluminum laminate film. After injecting an electrolyte, a negative electrode lead and a safety valve are installed, and the exterior material is sealed. The secondary battery obtained in this way has high adhesion between the electrode and the separator for a secondary battery, has excellent battery characteristics, and can be manufactured at low cost. EXAMPLES
[0101] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the following description, "%" and "parts" represent "% by mass" and "parts by mass". The measurement methods used in the examples are shown below.
[0102] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. Measurement methods used in the examples are as follows. [Measurement method] (1) Air permeability Using an Oken-type air permeability measuring device (EG01-5-1MR manufactured by Asahi Seiko Co., Ltd.), the central part of a 100 mm x 100 mm size was measured in accordance with JIS P 8117 (2009). The above measurement was performed on three samples, and the measured values were averaged, and this average value was taken as the air permeability (sec / 100 cc).
[0103] (2) Thickness of the porous layer The porous film was cut out to a size of 100 mm x 100 mm. Next, a cross section of the sample was cut out from the center of the sample using a microtome, and the cross section was observed at a magnification of 10,000 times using a field emission scanning electron microscope (S-800 manufactured by Hitachi, Ltd., accelerating voltage 26 kV). The highest point from the interface with the porous substrate was taken as the thickness, and in the case of one side, only one side was measured, and in the case of both sides, both sides were measured, and the total was taken as the film thickness of the porous layer. Regarding the interface between the porous substrate and the porous layer, the location where the inorganic particles were no longer confirmed in the region where the inorganic particles existed was defined as the interface. The above measurement was performed on five samples, and the measured values were averaged.
[0104] (3) Content of inorganic particles in the porous layer The porous layer was removed from a 10cm x 10cm porous film using 40g of water, and the water and organic solvents such as alcohol were thoroughly dried to obtain the components contained in the porous layer. After measuring the mass of all the components obtained, the components were burned at a high temperature at which the organic resin components melted and decomposed, and the mass of only the inorganic particles was measured. The content of inorganic particles in the porous layer was calculated in mass% using the formula (mass of inorganic particles / mass of all components) x 100.
[0105] (4) Glass transition temperature of organic resin A The midpoint glass transition temperature was measured by differential scanning calorimetry (DSC) according to the provisions of "JIS K7121:2012 Measurement method for transition temperature of plastics." The midpoint glass transition temperature was defined as the temperature at the point where a line equidistant in the vertical direction from the extended straight line of each baseline intersects with the curve of the step-like change in the glass transition.
[0106] (5) Organic resin content α, β, γ The porous layer measured in "(2) Film Thickness of Porous Layer" was divided into three parts, an outer layer, an intermediate layer, and an inner layer, and the organic resin contents α, β, and γ in each region were calculated using the following method. First, a cross section of the sample was cut out with a microtome, and a cross section SEM image and a cross section SEM-EDX image of carbon element in the same field of view were obtained at a magnification of 10,000 times with a field emission scanning electron microscope (S-800 manufactured by Hitachi, Ltd., acceleration voltage 26 kV). Next, the cross section SEM image was used to measure the film thickness of the porous layer according to "(2) Film Thickness of Porous Layer". The film thickness was divided into three parts, and each region of the outer layer, intermediate layer, and inner layer was determined. The cross section SEM image and the cross section SEM-EDX image of carbon element were superimposed, and each region of the outer layer, intermediate layer, and inner layer was compared with the cross section SEM-EDX image of carbon element. Each region of the outer layer, intermediate layer, and inner layer was analyzed. The analysis was performed as follows using image analysis software (Toyo Corporation, SPIP). For the HeightSensor image, the boundary of organic resin A was emphasized using a general-purpose plug-in (PrugIn_BoundaryDropper (Particle7x7)), and then the area of carbon elements included in the field of view was calculated using automatic threshold calculation, excluding the edges of the image. The organic resin content was calculated as follows: area of carbon element contained in the outer layer region × 100 / (area of carbon element contained in the entire region of the outer layer, middle layer, and inner layer). The same measurements were performed on five samples, and the average value was taken as the organic resin content α (%). The organic resin content was calculated as follows: area of carbon element contained in the middle layer region × 100 / (area of carbon element contained in the entire region of the outer layer, middle layer, and inner layer). The same measurements were performed on five samples, and the average value was taken as the organic resin content β (%). The organic resin content was calculated as follows: area of carbon element contained in the inner layer region × 100 / (area of carbon element contained in the entire region of the outer layer, middle layer, and inner layer). The same measurements were performed on five samples, and the average value was taken as the organic resin content γ (%).
[0107] (6) Coating appearance A sample measuring 100 x 200 mm was placed on black drawing paper, and the appearance of the coating was observed and evaluated based on the following criteria. Excellent coating appearance: No coating streaks or repelling - Coating appearance is good: coating streaks or coating cissing are slightly observed Appearance of coating film is acceptable: slight coating streaks and coating repellency are observed -Poor coating appearance: Coating streaks and coating cissing are observed, making evaluation difficult
[0108] (7) Heat shrinkage rate (thermal dimensional stability) For three samples measuring 100mm x 100mm, the length from the midpoint of one side to the midpoint of the opposite side was measured, and the samples were heat-treated in an oven at 150°C for 30 minutes without tension. After heat treatment, the samples were removed and the length between the midpoints at the same points as before heat treatment was measured, and the heat shrinkage rate was calculated using the following formula. Two points were calculated at the same time from one sample, and the average of all the values was taken as the heat shrinkage rate (thermal dimensional stability), with less than 5% being excellent, 5% to less than 10% being excellent, 10% to less than 20% being good, 20% to less than 40% being fair, and 40% or more being poor. Heat shrinkage rate (%) = [(length between midpoints before heat treatment - length between midpoints after heat treatment) / (length between midpoints before heat treatment)] x 100.
[0109] (8) Adhesion to substrate A transparent double-sided tape (3M, product number 665) cut to a width of 18 mm and a length of 100 mm was attached to a 2 cm thick acrylic plate. Next, a porous film cut to a length of 20 mm and 200 mm was roll-pressed at 0.5 MPa, 25°C, and 0.2 m / min to attach the transparent double-sided tape and the porous film. After that, the 180° peel adhesive strength was measured at a peel speed of 300 mm / min. -Excellent adhesive strength: The porous substrate and porous layer peeled off with greater force. -Excellent adhesive strength: The porous base material and the porous layer peeled off with strong force. Good adhesive strength: The porous base material and the porous layer peeled off with a somewhat strong force. · Good adhesive strength: The porous base material and the porous layer peeled off with a weak force. -Poor adhesive strength: The porous base material and the porous layer peeled off with very little force.
[0110] (9) Adhesion to electrodes The active material is Li(Ni 5 / 10 Mn 2 / 10 Co 3 / 10 )O2, vinylidene fluoride resin as binder, acetylene black and graphite as conductive additives, a positive electrode 15mm x 100mm, and a porous film were placed so that the active material and the porous layer were in contact, and heat pressed at 0.5MPa, 100℃, and 0.2m / min with a hot roll press machine, and the electrodes were manually peeled off using tweezers, and the adhesive strength was evaluated on the following four levels. Similarly, the adhesive strength between the negative electrode and the porous film, whose active material was graphite, whose binder was vinylidene fluoride resin, and whose conductive additive was carbon black, was also measured, and the average adhesive strength obtained by integrating the evaluation results of the positive and negative electrodes was determined as the adhesive strength. Excellent adhesive strength: The electrode and porous film peeled off with greater force. Excellent adhesive strength: The electrode and porous film peeled off when subjected to strong force. Good adhesive strength: The electrode and porous film peeled off with a somewhat strong force. · Good adhesive strength: The electrode and porous film peeled off with a weak force. -Poor adhesive strength: The electrode and porous film peeled off with very little force.
[0111] (10) Battery construction The positive electrode sheet contains Li(Ni 5 / 10 Mn 2 / 10 Co 3 / 10 A positive electrode slurry was prepared by dispersing 92 parts by mass of 10 ... 2 ). The positive electrode sheet was cut to a size of 40 mm x 40 mm. At this time, the current collecting tab adhesive portion without the active material layer was cut out to a size of 5 mm x 5 mm on the outside of the active material surface. An aluminum tab with a width of 5 mm and a thickness of 0.1 mm was ultrasonically welded to the tab adhesive portion. The negative electrode sheet was prepared by dispersing 98 parts by mass of natural graphite as the negative electrode active material, 1 part by mass of carboxymethyl cellulose as a thickener, and 1 part by mass of a styrene-butadiene copolymer as a negative electrode binder in water using a planetary mixer, applying the resulting negative electrode slurry onto copper foil, drying, and rolling (coating weight: 5.5 mg / cm). 2 ). The negative electrode sheet was cut to a size of 45 mm x 45 mm. At this time, the current collecting tab adhesive part without the active material layer was cut out to a size of 5 mm x 5 mm outside the active material surface. A copper tab of the same size as the positive electrode tab was ultrasonically welded to the tab adhesive part. Next, the porous film was cut to 55 mm x 55 mm, and the above positive and negative electrodes were placed on both sides of the porous film with the active material layer separating the porous film, and the positive electrode coating was arranged so that all the positive electrode coating parts faced the negative electrode coating parts to obtain an electrode group. The above positive electrode, porous film, and negative electrode were sandwiched between a single 90 mm x 200 mm aluminum laminate film, the long side of the aluminum laminate film was folded, and the two long sides of the aluminum laminate film were heat-sealed to form a bag shape. The electrolyte was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate:diethyl carbonate = 1:1 (volume ratio) to a concentration of 1 mol / L. 1.5 g of the electrolyte was poured into a bag-shaped aluminum laminate film, and the short sides of the aluminum laminate film were heat-sealed while the electrolyte was being impregnated under reduced pressure to form a laminated battery.
[0112] (11) Discharge load characteristics The discharge load characteristics were tested according to the following procedure and evaluated in terms of the discharge capacity retention rate. The laminated battery was used to measure the discharge capacity when discharged at 0.5C and at 10C at 25°C, and the discharge capacity retention rate was calculated by (discharge capacity at 10C) / (discharge capacity at 0.5C)×100. Here, the charging conditions were constant current charging at 0.5C and 4.3V, and the discharging conditions were constant current discharging at 2.7V. Five laminated batteries were produced, and the results with the maximum and minimum discharge capacity retention rates were removed, and the average of the measurement results was taken as the capacity retention rate. A discharge capacity retention rate of less than 40% was rated as poor, 45% to less than 50% was rated as good, 50% to less than 55% was rated as excellent, and 55% or more was rated as excellent.
[0113] (12) Charge / discharge cycle characteristics The charge / discharge cycle characteristics of the laminated battery were tested according to the following procedure, and evaluated in terms of discharge capacity retention rate. <Cycles 1 to 300> One cycle consisted of charging and discharging, and the charging conditions were a constant current charge of 2C and 4.3V, and the discharging conditions were a constant current discharge of 2C and 2.7V. The charging and discharging were repeated 300 times at 25°C. <Calculation of Discharge Capacity Retention Rate> The discharge capacity retention rate was calculated by (discharge capacity at the 300th cycle) / (discharge capacity at the 1st cycle) x 100. Five of the above laminated batteries were produced, and the results with the maximum and minimum discharge capacity retention rates were removed, and the average of the three measurement results was taken as the capacity retention rate. A discharge capacity retention rate of less than 50% was determined to be poor charge / discharge cycle characteristics, between 50% and 60% was determined to be good charge / discharge cycle characteristics, between 60% and 70% was determined to be excellent charge / discharge cycle characteristics, and 70% or more was determined to be excellent charge / discharge cycle characteristics.
[0114] Example 1 120 parts of ion-exchanged water and 1 part of Adeka Reasorb SR-1025 (emulsifier manufactured by Adeka Corporation) were charged into a reactor, and stirring was started. 0.4 parts of 2,2'-azobis(2-(2-imidazolin-2-yl)propane) (manufactured by Wako Pure Chemical Industries, Ltd.) were added to this under a nitrogen atmosphere, and a mixture consisting of 30 parts of 2,2,2-trifluoroethyl methacrylate (3FMA), 14 parts of 4-hydroxybutyl acrylate (4-HBA), 56 parts of cyclohexyl acrylate (CHA), 9 parts of Adeka Reasorb SR-1025 (emulsifier manufactured by Adeka Corporation), and 115 parts of ion-exchanged water was continuously dropped at 60 ° C. over 2 hours, and polymerization treatment was performed for 4 hours after the end of the dropwise addition, to produce dispersion A containing organic resin particles A (average particle size 170 nm, glass transition temperature 40 ° C.) consisting of an organic resin copolymer. Alumina particles (aluminum oxide) with an average particle size of 0.5 μm were used as the inorganic particles, and the same amount of water as the inorganic particles was added as the solvent, and 1% by mass of carboxymethyl cellulose was added as a dispersant relative to the inorganic particles. Dispersion B was prepared by dispersing the particles in a bead mill. Dispersion A and Dispersion B were dispersed in water so that the content of inorganic particles in the porous layer was 70 mass%, and mixed with a stirrer. Further, an acrylic emulsion binder (acrylic particles, 100 nm) was added as a binder in an amount of 17 mass% based on the total amount of organic resin particles A and inorganic particles, to prepare a coating liquid. The obtained coating liquid was applied to both sides of a polyethylene porous substrate (thickness 9 μm, air permeability 60 sec / 100 cc) using a wire bar, and dried in a hot air oven (drying temperature setting 50 ° C) for 1 minute, and the solvent contained therein was evaporated to form a porous layer, thereby obtaining a porous film of the present invention. For the obtained porous film, the measurement results of the film thickness, air permeability, organic resin content α, organic resin content β, organic resin content γ, coating appearance, heat shrinkage rate (thermal dimensional stability), adhesion to the porous substrate, adhesion to the electrode, discharge load characteristics, and charge / discharge cycle characteristics are shown in Table 2.
[0115] Example 2 The porous film of the present invention was obtained in the same manner as in Example 1, except that the composition ratio of the organic resin particles A was changed to 30 parts of 2,2,2-trifluoroethyl methacrylate (3FMA), 2 parts of 4-hydroxybutyl acrylate (4-HBA), 7 parts of alkylene glycol dimethacrylate (PDE-600 manufactured by NOF Corp., homopolymer Tg: -34°C), and 68 parts of cyclohexyl acrylate (CHA) as shown in Table 1-1. The measurement results of the porous film are shown in Table 2.
[0116] Example 3 A porous film of the present invention was obtained in the same manner as in Example 2, except that the thickness of the porous layer was set to the thickness shown in Table 2. The measurement results of the porous film are shown in Table 2.
[0117] Example 4 A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-1. The measurement results of the porous film are shown in Table 2.
[0118] Example 5 A porous film of the present invention was obtained in the same manner as in Example 4, except that the thickness of the porous layer was set to the thickness shown in Table 2. The measurement results of the porous film are shown in Table 2.
[0119] Example 6 A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-1. The measurement results of the porous film are shown in Table 2.
[0120] Example 7 A porous film of the present invention was obtained in the same manner as in Example 6, except that the thickness of the porous layer was set to the thickness shown in Table 2. The measurement results of the porous film are shown in Table 2.
[0121] Example 8 A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-1. The measurement results of the porous film are shown in Table 2.
[0122] Example 9 A porous film of the present invention was obtained in the same manner as in Example 8, except that the thickness of the porous layer was set to the thickness shown in Table 2. The measurement results of the porous film are shown in Table 2.
[0123] Example 10 A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-1. The measurement results of the porous film are shown in Table 2.
[0124] Example 11 A porous film of the present invention was obtained in the same manner as in Example 10, except that the thickness of the porous layer was set to the thickness shown in Table 2. The measurement results of the porous film are shown in Table 2.
[0125] Example 12 A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-2. The measurement results of the porous film are shown in Table 2.
[0126] Example 13 A porous film of the present invention was obtained in the same manner as in Example 8, except that organic resin particles B (polyethylene, melting point 80° C.) were added in an amount of 2.2 mass % based on the total amount of organic resin particles A and inorganic particles. The measurement results of the porous film are shown in Table 2.
[0127] Example 14 A porous film of the present invention was obtained in the same manner as in Example 8, except that crumb-like organic resin A was used instead of particles. The measurement results of the porous film are shown in Table 2.
[0128] Example 15 A porous film of the present invention was obtained in the same manner as in Example 8, except that organic resin particles B (polypropylene, melting point 60° C.) were added in an amount of 2.2 mass % based on the total amount of organic resin particles A and inorganic particles. The measurement results of the porous film are shown in Table 2.
[0129] (Example 16) A porous film of the present invention was obtained in the same manner as in Example 8, except that the content of inorganic particles in the porous layer was 55 mass %. The measurement results of the porous film are shown in Table 2. The measurement results of the porous film are shown in Table 2.
[0130] (Example 17) A porous film of the present invention was obtained in the same manner as in Example 8, except that the content of inorganic particles contained in the porous layer was 90 mass%, and the content of the acrylic emulsion binder (acrylic particles, 100 nm) was 7.5 mass% relative to the total amount of the organic resin particles A and the inorganic particles. The measurement results of the porous film are shown in Table 2. The measurement results of the porous film are shown in Table 2.
[0131] (Example 18) Except for using barium sulfate as the inorganic particles, the porous film of the present invention was obtained in the same manner as in Example 8. The measurement results of the porous film are shown in Table 2.
[0132] (Example 19) A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-2. The measurement results of the porous film are shown in Table 2.
[0133] (Example 20) A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-2, and the thickness of the porous layer was changed to the thickness shown in Table 2. The measurement results of the porous film are shown in Table 2.
[0134] Example 21 A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-2. The measurement results of the porous film are shown in Table 2.
[0135] Example 22 A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-2, and the thickness of the porous layer was changed to the thickness shown in Table 2. The measurement results of the porous film are shown in Table 2.
[0136] Example 23 A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-3. The measurement results of the porous film are shown in Table 2.
[0137] (Example 24) A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-3 and the thickness of the porous layer was changed to the thickness shown in Table 2. The measurement results of the porous film are shown in Table 2.
[0138] (Example 25) A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-3. The measurement results of the porous film are shown in Table 2.
[0139] (Example 26) A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-3, and the thickness of the porous layer was changed to the thickness shown in Table 2. The measurement results of the porous film are shown in Table 2.
[0140] Example 27 A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-3. The measurement results of the porous film are shown in Table 2.
[0141] (Example 28) A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-3, and the thickness of the porous layer was changed to the thickness shown in Table 2. The measurement results of the porous film are shown in Table 2.
[0142] (Example 29) A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-3. The measurement results of the porous film are shown in Table 2.
[0143] (Example 30) A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-3, and the thickness of the porous layer was changed to the thickness shown in Table 2. The measurement results of the porous film are shown in Table 2.
[0144] (Example 31) A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-3. The measurement results of the porous film are shown in Table 2.
[0145] Example 32 A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-3. The measurement results of the porous film are shown in Table 2.
[0146] (Example 33) A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-3. The measurement results of the porous film are shown in Table 2.
[0147] (Example 34) A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition of the organic resin particles A was changed to the composition shown in Table 1-4. The measurement results of the porous film are shown in Table 2.
[0148] Comparative Example 1 A porous film was obtained in the same manner as in Example 1, except that the composition ratio of the organic resin particles A was changed to the composition shown in Table 1-4. The measurement results of the porous film are shown in Table 2.
[0149] Comparative Example 2 A porous film was obtained in the same manner as in Example 1, except that the composition ratio of the organic resin particles A was changed to the composition shown in Table 1-4. The measurement results of the porous film are shown in Table 2.
[0150] Comparative Example 3 The organic particles A were prepared in the same manner as in Example 1, except that the composition ratio of the organic resin particles A was changed to the composition shown in Table 1-4. However, stable particles could not be obtained. Therefore, a porous layer could not be formed, and a porous film could not be measured.
[0151] Comparative Example 4 A porous film was obtained in the same manner as in Example 1, except that the composition was changed to that shown in Table 1-4 without using the organic resin particles A. The measurement results of the porous film are shown in Table 2.
[0152] From Tables 1-1, 1-2, 1-3, 1-4 and 2, it can be seen that all of Examples 1 to 34 have a porous substrate and a porous layer on at least one side of the porous substrate, which contains inorganic particles and an organic resin that is adhesive to electrodes, and the porous layer is divided into three equal parts in the thickness direction, that is, an inner layer, an intermediate layer and an outer layer, satisfying the following relative to the total organic resin content: (a) the content α of the organic resin present in the outer layer is 30% or more and 60% or less, (b) the content β of the organic resin present in the intermediate layer is 10% or more and 25% or less, and (c) the content γ of the organic resin present in the inner layer is 30% or more and 60% or less. Therefore, sufficient thermal dimensional stability, adhesion to the electrodes and good battery characteristics can be obtained.
[0153] On the other hand, in Comparative Example 1, the organic resin content α of the outer layer is less than 30% by mass, and the organic resin content β of the intermediate layer is more than 25% by mass, so that the adhesion to the electrode is poor. In Comparative Example 2, the organic resin content γ of the inner layer is less than 30% by mass, and the organic resin content β of the intermediate layer is more than 25% by mass, so that the adhesion between the porous substrate and the porous layer is insufficient, and therefore sufficient adhesion to the electrode is not obtained. In Comparative Example 3, the content of the (meth)acrylate monomer having a hydroxyl group exceeds 30% by mass, so that a stable organic resin A cannot be obtained. A porous layer cannot be formed with this organic resin A. In Comparative Example 4, the porous layer does not contain an organic resin, so that sufficient adhesion to the electrode and sufficient adhesion to the porous substrate are not obtained.
[0154] [Table 1-1]
[0155] [Table 1-2]
[0156] [Table 1-3]
[0157] [Table 1-4]
[0158] [Table 2]
Claims
1. A porous film for use in a separator for a secondary battery, comprising: a porous substrate; and a porous layer containing inorganic particles and an organic resin on at least one surface of the porous substrate, the porous layer being divided into three equal parts in the thickness direction into an inner layer in contact with the porous substrate, an intermediate layer adjacent to the inner layer, and an outer layer adjacent to the intermediate layer, the porous film satisfying the following (a) to (c), and the organic resin being a mixture containing a polymer containing a fluorine-containing (meth)acrylate monomer, or an organic resin A having a copolymer containing a fluorine-containing (meth)acrylate monomer. (a) The content α of the organic resin present in the outer layer is 30% or more and 60% or less of the total organic resin content. (b) the content β of the organic resin present in the intermediate layer is 10% or more and 25% or less of the total content of the organic resins. (c) the content γ of the organic resin present in the inner layer is 30% or more and 60% or less of the content of all organic resins.
2. 2. The porous film according to claim 1, wherein the organic resin is organic resin particles.
3. The porous film according to claim 1 or 2, wherein the organic resin further comprises a binder.
4. The binder is at least one binder selected from the group consisting of polyamide, polyamideimide, polyimide, polyetherimide, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, polysulfone, polyketone, polyether ketone, polycarbonate, polyacetal, polyvinyl alcohol, polyethylene glycol, cellulose ether, acrylic resin, polyethylene, polypropylene, polystyrene, and urethane. The porous film according to claim 3.
5. The porous film according to claim 3 or 4, wherein the binder is an acrylic resin.
6. The organic resin A is a mixture containing a polymer composed of a fluorine-containing (meth)acrylate monomer and a polymer composed of a (meth)acrylate monomer having a hydroxyl group, or a copolymer containing a fluorine-containing (meth)acrylate monomer and a (meth)acrylate monomer having a hydroxyl group, and the content of the (meth)acrylate monomer having a hydroxyl group is 1% by mass or more and 30% by mass or less when the total components of the organic resin A are 100% by mass. The porous film according to any one of claims 1 to 5.
7. The porous film according to claim 6, wherein the (meth)acrylate monomer having a hydroxyl group has a glass transition temperature of a homopolymer formed from the monomer of -100°C or higher and 0°C or lower.
8. The organic resin A further contains a monomer having two or more reactive groups per molecule, and the content of the monomer having two or more reactive groups per molecule contained in the organic resin A is 1% by mass or more and 10% by mass or less. The porous film according to claim 6 or 7.
9. The porous film according to claim 8, wherein the monomer having two or more reactive groups per molecule is an alkylene glycol di(meth)acrylate or a urethane di(meth)acrylate.
10. The porous film according to any one of claims 1 to 9, wherein the organic resin contains an organic resin B that does not contain fluorine.
11. The content of inorganic particles contained in the porous layer is 60% by mass or more and 95% by mass or less when the total constituent components of the porous layer are 100% by mass. The porous film according to any one of claims 1 to 10.
12. A separator for a secondary battery, comprising the porous film according to any one of claims 1 to 11.
13. A secondary battery comprising the separator for a secondary battery according to claim 12.
Citation Information
Patent Citations
Pedal mechanism for bicycle
JP1981047378A
Driving controller for moving type incore calibrator
JP1986091597A
Separator and method of manufacturing the same, and lithium secondary battery including the separator
JP2013235824A
Nonaqueous electrolyte secondary battery
JP2017054725A
Porous film, separator for secondary battery, and secondary battery
JP2020077618A